PENGARUH WORK LIFE BALANCE DAN GAYA KEPEMIMPINAN DEMOKRATIS TERHADAP KINERJA PEGAWAI DAMKAR BENGKULU SELATAN - Ferdy Ardison; Eti Arini (UM. Bengkulu, 2026)
Performance is a very important part in achieving company goals. Employee performance is influenced by many factors including work life balance and leadership style. The purpose of this study was to determine the effect of work life balance and leadership style democratic on employee performance in the South Bengkulu Fire Department. This research was conducted at the South Bengkulu Fire Department. The type of research used in this study was quantitative descriptive. The sample in this study was 77 people with the sampling technique in this study was total sampling. Data collection techniques were observation, questionnaires and documentation. The data analysis technique used in this study was quantitative descriptive. The results showed that work life balance had a significant effect on employee performance in the South Bengkulu Fire Department with a calculated t value> t table (2.582> 1.66600) and (sig a = 0.012 <0.050). Leadership style had a significant effect on employee performance with a calculated t value> t table (3.368> 1.66600) and (sig a = 0.001 <0.050). The results of the F test show that the F count value is 44.376 > 3.12 with a significance value of 0.000 < 0.050, which means that there is a significant simultaneous influence of the work life balance and leadership style democratic variables on employee performance in the Bengkulu Selatan Fire Department environment. The R Square value is 0.545, this means that the rise and fall of the dependent variable, namely employee performance, is influenced by the independent variables, namely work life balance and leadership style by 54.5%, while the remaining 45.5% is influenced by other variables. Keywords: Work Life Balance and Leadership Style Democratic, Performance